Impact of help-seeking behavior and partner support on postpartum depression among Saudi women - Almutairi AF; Salam M; Alanazi S; Alweldawi M; Alsomali N; Alotaibi N (Neuropsychiatric Disease and Treatment, 2017)
Adel F Almutairi,1,2 Mahmoud Salam,1,2 Samiyah Alanazi,1 Manal Alweldawi,1 Najad Alsomali,1 Najla Alotaibi1 1King Saud Bin Abdulaziz University of Health Sciences, 2Science and Technology Unit, King Abdullah International Medical Research Center, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia Background: Many studies have discovered a number of factors that can contribute to the risk of developing postpartum depression (PPD), including, but not limited to, life stressors, lack of social support, low economic status, and quality of the marital relationship. However, these studies were conducted in various countries with participants from different cultural backgrounds.Purpose: This study aimed to examine the impact of general help-seeking behavior (GHSB) and partner support (PS) on PPD among Saudi women in primary health care clinics in Riyadh city.Methods: Data were collected by using self-administered measures of the Edinburgh Postnatal Depression Scale (EPDS), General Help-Seeking Questionnaire (GHSQ), and Partner Support Scale (PSS). Frequency distribution was used to analyze the categorical data, and Student’s t-test and one-way analysis of variance were employed to compare the numerical data. Linear regression analysis was used to control for all confounders.Results: The findings showed that 9% and 28% of women had good and poor GHSB, respectively, 16% had poor PS, and 25.7% could be classified as probably depressed. Negative relationships between GHSB versus PPD and PS versus PPD were observed. Adjusting by mode of delivery and controlling for confounders in linear regression showed that women who underwent normal vaginal delivery, with higher para rates (β=0.250, t=2.063) and lower PS scores (β=-0.238, t=-2.038), were more likely to suffer higher depression scores (adj P=0.043 and adj P=0.045, respectively). Women who underwent cesarean-section, with postpartum duration ≥6 weeks (β=0.374, t=2.082), were more likely to suffer higher depression scores (adj P=0.045) compared to those with <6 weeks of postpartum duration.Conclusion: The prevalence of PPD among the study participants was high, especially among higher para women who underwent normal delivery and women ≥6 weeks post cesarean-section, in comparison with the results in other studies. PPD is reduced by enhancing women’s GHSB and PS. Keywords: postpartum depression, partner support, help-seeking, women, Saudi Arabia